Silver nanoparticle / cuprous selenide composite catalyst and preparation method and application thereof
By loading the composite catalyst prepared by silver nanoparticles on the selenium copper, the problem of low efficiency of carbon dioxide reduction to C2+products is solved, and efficient ethanol production has been achieved, and it has good catalytic performance and stability.
Patent Information
- Application Number
- CN202411414438.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The challenge of developing efficient electrocatalytic catalysts to achieve carbon dioxide reduction to C2+ products, especially due to the low controllability of C-C coupling and the low activation energy barrier of ethylene, hindering the effectiveness of this reaction system.
A silver nanoparticle/cuprous selenide composite catalyst is used, and silver nanoparticles are loaded on cuprous selenide through electrodeposition technology to form a composite catalyst. The catalyst is based on flower rod-shaped silver selenide formed by chemical oxidation treatment of copper foam, and is prepared through specific chemical treatment and electrochemical deposition methods.
Achieving high-efficiency electric catalytic carbon dioxide reduction under low potential, especially under -0.52V (VS.RHE), silver nanoparticles/selenium copper composite catalysts reached 70.1 % Faraday efficiency, which has high selectivity to ethanol, and it is highly selective. The activity of catalysts is high and stable.
Smart Images

Figure CN119352080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a silver nanoparticle / cuprous selenide composite catalyst and a preparation method and application thereof. Background Art
[0002] Among various carbon dioxide reduction products, C 2+ The product has attracted much attention due to its higher energy density and economic value compared to C1 products. As a liquid oxygenated C2 product that is easy to store and transport, ethanol has been widely used as a solvent and raw material for the production of organic chemicals and disinfectants.
[0003] However, the development of efficient electrocatalysts remains a challenge. The reduction of CO to C is difficult due to the low controllability of CC coupling. 2+ Even if the CC coupling is successful, due to the 2+ The low activation barrier and the major production of ethylene, which is common in the reduction of carbon dioxide, still hinder this reaction system. Controlling the evolution of reaction intermediates is the key to overcome this limitation and relies on catalyst design. Copper is an effective catalyst for the reduction of carbon dioxide to prepare multi-carbon products, but is usually limited by low activity and selectivity due to its high surface mobility and low cohesive energy. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a silver nanoparticle / cuprous selenide composite catalyst that can efficiently electrocatalyze the reduction of carbon dioxide; another purpose of the present invention is to provide a preparation method and application of the silver nanoparticle / cuprous selenide composite catalyst.
[0005] Technical solution: The silver nanoparticle / cuprous selenide composite catalyst of the present invention is composited by cuprous selenide loaded with silver nanoparticles through electrodeposition, wherein the cuprous selenide is formed by treating foamed copper with a chemical oxidation method.
[0006] Preferably, the cuprous selenide is in the shape of a flower rod.
[0007] Preferably, the mass ratio of the silver nanoparticles in the silver nanoparticle / cuprous selenide composite catalyst is 2.1-3.3%.
[0008] Further preferably, the mass ratio of silver nanoparticles in the silver nanoparticle / cuprous selenide composite catalyst is 2.69%.
[0009] The preparation method of the silver nanoparticle / cuprous selenide composite catalyst of the present invention comprises the following steps:
[0010] (1) placing the copper foam in acetone, hydrochloric acid and deionized water in turn and performing ultrasonic treatment to remove the oily substance and oxide layer on the surface of the copper foam;
[0011] (2) preparing a mixed solution of sodium hydroxide and ammonium persulfate, and stirring and mixing;
[0012] (3) soaking the copper foam treated in step (1) in the mixed solution obtained in step (2) to react until a layer of blue copper hydroxide is visible on the surface of the copper foam;
[0013] (4) extracting the product in step (3), rinsing, and vacuum drying;
[0014] (5) adding selenium powder, sodium borohydride and potassium hydroxide into deionized water, stirring and mixing at 40 to 60° C. to obtain a mixed solution;
[0015] (6) placing the material obtained in step (4) into the mixed solution obtained in step (5), reacting at 100 to 150° C. for 4 to 6 hours, and then cooling to room temperature;
[0016] (7) separating the product obtained in step (6), washing, and drying to obtain cuprous selenide;
[0017] (8) Connecting the cuprous selenide obtained in step (7) as a working electrode to a three-electrode system, performing a scanning CV test, and reactivating the cuprous selenide; subsequently, applying a constant current to the cuprous selenide, with a deposition time of 30 to 180 seconds, to obtain a silver nanoparticle / cuprous selenide composite catalyst.
[0018] Preferably, in step (1), the concentration of hydrochloric acid is 0.5 to 2 mol / L.
[0019] Preferably, in step (2), the concentration of sodium hydroxide in the mixed solution is 0.8 to 1.2 mol / L, and the concentration of ammonium persulfate is 0.05 to 0.1 mol / L, and the mixture is mixed for 5 to 10 minutes under magnetic stirring.
[0020] Preferably, the reaction time in step (3) is 2 to 10 minutes.
[0021] Preferably, the rinsing in step (4) is performed by rinsing with deionized water for 2 to 3 times, and the vacuum drying is performed in a vacuum oven at a temperature of 60°C.
[0022] Preferably, in the step (5), the concentration of selenium powder in the mixed solution is 0.02-0.05 mol / L, the concentration of sodium borohydride is 0.05-0.1 mol / L, and the concentration of potassium hydroxide is 0.02-0.05 mol / L. The mixed solution is heated to 40-60° C. under magnetic stirring and stirred for 20-30 minutes.
[0023] Preferably, the specific method of step (6) is: 50 to 100 ml of the mixed solution of step (5) is loaded into a 100 ml Teflon stainless steel reactor, the material obtained in step (4) is placed therein, reacted at 100 to 150° C. for 4 to 6 hours, and then naturally cooled to room temperature.
[0024] Further preferably, the specific method of step (6) is: 50 to 100 ml of the mixed solution of step (5) is loaded into a 100 ml Teflon stainless steel reactor, the material obtained in step (4) is placed therein, reacted at 120° C. for 4 to 6 hours, and then naturally cooled to room temperature.
[0025] Preferably, the specific method of step (7) is: separating the product obtained in step (6), washing it with deionized water for 2 to 3 times, and drying it at a temperature of 50 to 70° C. for 8 to 12 hours under vacuum conditions to obtain cuprous selenide.
[0026] Preferably, the specific method of step (8) is: preparing a mixed solution of citric acid trihydrate, silver nitrate and sulfuric acid, stirring and dispersing; connecting the cuprous selenide obtained in step (7) as a working electrode to a three-electrode system consisting of a saturated calomel reference electrode and a platinum counter electrode, and using the mixed solution of citric acid trihydrate, silver nitrate and sulfuric acid as an electrolyte; performing a scanning CV test to reactivate the cuprous selenide; then, applying a constant current to the cuprous selenide, with a deposition time of 30 to 180 seconds, to obtain a silver nanoparticle / cuprous selenide composite catalyst.
[0027] Preferably, the concentration of citric acid trihydrate in the mixed solution is 0.1 to 0.2 mol / L, the concentration of silver nitrate is 1.5 to 2.5 mol / L, and the concentration of sulfuric acid is 0.1 to 0.2 mol / L, and the mixture is stirred for 10 to 30 minutes.
[0028] Preferably, the range of the scanning CV test in step (8) is 0.2 to -0.8 V (vs. SHE), and the constant current applied to the cuprous selenide is 15 to 30 mA.
[0029] Further preferably, the deposition time in step (8) is 90 s.
[0030] The invention discloses an application of the silver nanoparticle / cuprous selenide composite catalyst in the preparation of a catalytic electrode.
[0031] The invention discloses an application of the silver nanoparticle / cuprous selenide composite catalyst in the electrocatalytic reduction of carbon dioxide.
[0032] The invention discloses an application of the silver nanoparticle / cuprous selenide composite catalyst in the electrocatalytic reduction of carbon dioxide to produce ethanol.
[0033] The operation process of the silver nanoparticle / cuprous selenide composite catalyst detection of the present invention is as follows:
[0034] a) Prepare a silver nanoparticle / cuprous selenide structure composite catalyst working electrode, seal the catalyst with epoxy resin adhesive, and precisely control the actual contact area between the catalyst and the electrolyte (1 square centimeter). Construct a three-electrode electrocatalytic system, that is, select a platinum sheet electrode as the counter electrode and a silver chloride electrode as the reference electrode;
[0035] b) Before the electrocatalytic test, the cathode cell was aerated at a flow rate of 180-200 sccm for 25-30 minutes to saturate the electrolyte, and a certain flow rate was maintained during the test; 40-45 ml of 0.5 mol / L potassium bicarbonate electrolyte was added to the cathode and anode reaction cells respectively;
[0036] c) The three-electrode system was placed in a potassium bicarbonate solution, and the electrocatalytic carbon dioxide reduction performance of the silver nanoparticle / cuprous selenide composite catalyst was determined by linear sweep voltammetry under two different conditions: argon saturation and carbon dioxide saturation. The Faradaic efficiency of the silver nanoparticle / cuprous selenide composite catalyst for the electrocatalytic carbon dioxide reduction of ethanol was also tested.
[0037] Preferably, in step b), the flow rate of carbon dioxide is 25-35 sccm, and the concentration of potassium bicarbonate is 0.45-0.55 mol / L.
[0038] Preferably, the potential range of the linear sweep voltammetry in step c) is -1.5 to 0.1V.
[0039] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The present invention successfully synthesizes the silver nanoparticle / cuprous selenide composite catalyst by chemical oxidation, hydrothermal method and constant potential deposition method, and the synthesis is simple and inexpensive; 2. The silver nanoparticle / cuprous selenide composite catalyst synthesized by the present invention has high catalytic reaction activity, stable catalytic performance, good carbon dioxide reduction effect, and high selectivity for ethanol, especially when the silver deposition time is 90 seconds, the 90-silver nanoparticle / cuprous selenide composite catalyst obtains the best electrocatalytic carbon dioxide reduction ethanol performance; this strategy of nanoparticle modification interface balances the Cu on the catalyst surface δ+ active valence state, causing the enriched *CO to migrate to Cu δ+ Active sites accelerate the asymmetric coupling of *CO and *CHO. At a low potential of -0.52V (vs.RHE), the silver nanoparticle / cuprous selenide structure achieved a 70.1% Faraday efficiency for electrocatalytic carbon dioxide reduction of ethanol and an ethanol separation current of 13.9mA. Compared with existing catalysts, its overpotential is lower, the ethanol separation current is larger, and it has good ethanol selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a scanning electron microscope image of the silver nanoparticle / cuprous selenide composite catalyst of Example 2 of the present invention;
[0041] Figure 2 is an X-ray diffraction pattern of the silver nanoparticle / cuprous selenide composite catalyst of Example 3 of the present invention;
[0042] Figure 3 The linear voltammetric curves of each catalyst of Example 4 of the present invention under different gas conditions;
[0043] Figure 4 This is a Faraday efficiency distribution diagram of the product of the silver nanoparticle / cuprous selenide composite catalyst of Example 5 of the present invention at various potentials under carbon dioxide conditions;
[0044] Figure 5 This is the Faraday efficiency distribution diagram of ethanol products of each catalyst in Example 5 of the present invention under carbon dioxide conditions. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0046] Example 1
[0047] (1) First, the copper foam was placed in acetone, 0.5 mol / L hydrochloric acid, and deionized water, respectively, and ultrasonically treated for 10 minutes each to remove the oily substances and oxide layer on the surface;
[0048] (2) Then, add 3.2 g of sodium hydroxide and 1.2 g of ammonium persulfate to 100 ml of water and mix under magnetic stirring for about 10 minutes;
[0049] (3) soaking the copper foam prepared in step (1) in the mixed solution prepared in step (2) for 10 minutes, and a layer of blue copper hydroxide is visible on the surface of the copper foam;
[0050] (4) The material in (3) was then extracted, rinsed with deionized water three times, and dried in a vacuum oven at 60°C;
[0051] (5) 0.156 g of selenium powder, 0.178 g of sodium borohydride and 0.115 g of potassium hydroxide were added to 100 ml of deionized water, and the solution was heated to 60 degrees Celsius and stirred for 20 minutes;
[0052] (6) The mixed solution of step (5) was placed into a 100 ml Teflon stainless steel reactor, the material of step (4) was placed therein, and heated in an oven at 150 degrees Celsius for 4 hours, and then naturally cooled to room temperature;
[0053] (7) The product obtained in step (6) was rinsed with deionized water three times, and dried in a vacuum oven at 70 degrees Celsius for 8 hours to obtain cuprous selenide;
[0054] (8) 0.1 mol / L citric acid trihydrate, 2.0 mol / L silver nitrate and 0.1 mol / L sulfuric acid were mixed and stirred for 30 minutes to fully disperse them;
[0055] (9) The cuprous selenide prepared in step (7) is connected as a working electrode to a three-electrode system consisting of a saturated calomel reference electrode and a platinum counter electrode, and the mixed solution in step (8) is used as an electrolyte; the catalyst is reactivated by a scanning CV test in the range of 0.2 to -0.8 V (vs. SHE); then, a constant current of 30 mA is applied to the catalyst, and the deposition time is 60 s.
[0056] Example 2
[0057] (1) First, the copper foam was placed in acetone, 2 mol / L hydrochloric acid, and deionized water in turn, and each was ultrasonically treated for 10 minutes to remove the oily substances and oxide layer on the surface;
[0058] (2) Then, 4.4 g of sodium hydroxide and 2.28 g of ammonium persulfate were added to 100 ml of water and mixed under magnetic stirring for about 10 minutes;
[0059] (3) soaking the copper foam prepared in step (1) in the mixed solution prepared in step (2) for 5 minutes, and a layer of blue copper hydroxide is visible on the surface of the copper foam;
[0060] (4) The material in (3) was then extracted, rinsed with deionized water three times, and dried in a vacuum oven at 60°C;
[0061] (5) 0.39 g of selenium powder, 0.376 g of sodium borohydride and 0.28 g of potassium hydroxide were added to 100 ml of deionized water, and the solution was heated to 40 °C and stirred for 30 minutes;
[0062] (6) The mixed solution of step (5) was placed into a 100 ml Teflon stainless steel reactor, the material of step (4) was placed therein, and heated in an oven at 100 degrees Celsius for 6 hours, and then naturally cooled to room temperature;
[0063] (7) The product obtained in step (6) was rinsed with deionized water three times, and dried in a vacuum oven at 50 degrees Celsius for 12 hours to obtain cuprous selenide;
[0064] (8) 0.1 mol / L citric acid trihydrate, 2.0 mol / L silver nitrate and 0.1 mol / L sulfuric acid were mixed and stirred for 10 minutes to fully disperse them;
[0065] (9) The cuprous selenide prepared in step (7) is connected as a working electrode to a three-electrode system consisting of a saturated calomel reference electrode and a platinum counter electrode, and the mixed solution in step (8) is used as an electrolyte; the catalyst is reactivated by a scanning CV test in the range of 0.2 to -0.8 V (vs. SHE); then, a constant current of 15 mA is applied to the catalyst, and the deposition time is 90 s.
[0066] Figure 1 This is a scanning electron microscope image of the silver nanoparticle / cuprous selenide composite catalyst prepared by the present invention.
[0067] Embodiment 3:
[0068] (1) First, the copper foam was placed in acetone, 1.0 mol / L hydrochloric acid, and deionized water in turn, and each was ultrasonically treated for 10 minutes to remove the oily substances and oxide layer on the surface;
[0069] (2) Then, add 3.9 g of sodium hydroxide and 1.75 g of ammonium persulfate to 100 ml of water and mix under magnetic stirring for about 10 minutes;
[0070] (3) soaking the copper foam prepared in step (1) in the mixed solution prepared in step (2) for 5 minutes, and a layer of blue copper hydroxide is visible on the surface of the copper foam;
[0071] (4) The material in (3) was then extracted, rinsed with deionized water three times, and dried in a vacuum oven at 60°C;
[0072] (5) 0.156 g of selenium powder, 0.376 g of sodium borohydride and 0.115 g of potassium hydroxide were added to 100 ml of deionized water, and the solution was heated to 50 °C and stirred for 30 minutes;
[0073] (6) The mixed solution of step (5) was placed into a 100 ml Teflon stainless steel reactor, the material of step (4) was placed therein, and heated in an oven at 120 degrees Celsius for 6 hours, and then naturally cooled to room temperature;
[0074] (7) The product obtained in step (6) was rinsed with deionized water three times, and dried in a vacuum oven at 60 degrees Celsius for 12 hours to obtain cuprous selenide;
[0075] (8) 0.1 mol / L citric acid trihydrate, 2.0 mol / L silver nitrate and 0.1 mol / L sulfuric acid were mixed and stirred for 10 minutes to fully disperse them;
[0076] (9) The cuprous selenide prepared in step (7) is connected as a working electrode to a three-electrode system consisting of a saturated calomel reference electrode and a platinum counter electrode, and the mixed solution in step (8) is used as an electrolyte; the catalyst is reactivated by a scanning CV test in the range of 0.2 to -0.8 V (vs. SHE); then, a constant current of 20 mA is applied to the catalyst, and the deposition time is maintained at 30, 90 and 180 s, respectively, to obtain silver nanoparticle / cuprous selenide composite catalysts, which are named 30-silver / cuprous selenide, 90-silver / cuprous selenide and 180-silver / cuprous selenide, respectively.
[0077] Figure 2 The crystal structure of the silver nanoparticle / cuprous selenide composite catalyst indicates that the composite catalyst is composed of cuprous selenide and silver.
[0078] Embodiment 4:
[0079] The electrocatalytic system adopts the traditional three-electrode system, that is, the platinum electrode is selected as the counter electrode, the silver chloride electrode is selected as the reference electrode, and the silver nanoparticle / cuprous selenide composite catalyst is selected as the working electrode. Before the electrocatalytic test, the cathode cell was aerated at a flow rate of 200sccm for 30 minutes to saturate the electrolyte, and the flow rate was maintained at 25sccm during the test. 40 ml of 0.5 mol / L potassium bicarbonate electrolyte was added to the cathode and anode reaction cells respectively, and the catalyst was sealed with epoxy resin adhesive to accurately control the actual contact area between the catalyst and the electrolyte (1 square centimeter). The three-electrode system was placed in a 0.5M potassium bicarbonate solution, and the electrocatalytic carbon dioxide reduction performance of the silver nanoparticle / cuprous selenide composite catalyst was determined by linear sweep voltammetry under two different conditions of argon saturation and carbon dioxide saturation. The carbon dioxide reduction performance of foam copper and cuprous selenide under the same conditions was compared.
[0080] Figure 3 The figure shows the current changes of copper foam, cuprous selenide, 30-silver / cupper selenide, 90-silver / cupper selenide and 180-silver / cupper selenide under carbon dioxide and argon conditions. The figure shows that compared with copper foam and cuprous selenide, silver nanoparticles / cupper selenide have higher current density under argon saturation or carbon dioxide saturation, and 90-silver / cupper selenide has the highest current density.
[0081] Embodiment 5:
[0082] The gas phase products were analyzed by online gas chromatography, with argon as the carrier gas. The quantification of the gas products was performed by mixing the gases to obtain a standard curve when the TCD detector was used for the quantitative analysis of hydrogen, and the FID-1 detector was used for the quantitative analysis of acetylene, ethylene, methane and carbon monoxide. A steady flow bottle was used at the front end of the chromatogram to filter and dehumidify the gas, and the flow of carbon dioxide was controlled by a gas flow mass controller. After a reaction period of 30 minutes, the liquid product was filtered to remove larger impurities. The liquid was injected into the chromatogram with a 1.0mL syringe, and the ethanol was quantified with a high-precision FID-2 detector. Standard solutions of 10, 25, 50, and 100 ppm ethanol were added to the chromatogram to obtain a standard curve for ethanol. The concentration of formate was analyzed by an ion chromatograph, and a standard curve for formate was obtained in 0, 5, 25, 50, and 100 ppm sodium formate standard solutions.
[0083] The three-electrode system was placed in a 0.5M potassium bicarbonate solution, and the Faradaic efficiency of the silver nanoparticle / cuprous selenide composite catalyst for electrocatalytic carbon dioxide reduction of various products was detected under carbon dioxide saturated conditions.
[0084] Figure 4 The Faradaic efficiency distribution diagram of the products of the 90-silver / cuprous selenide composite catalyst at various potentials under carbon dioxide conditions is shown, wherein the Faradaic efficiency of the 90-silver / cuprous selenide composite catalyst for ethanol increases with the increase of the applied test potential, reaching 41.44% at -0.47V, and exhibiting the best Faradaic efficiency of 70.1% at -0.52V (vs. RHE).
[0085] Based on Example 5, the Faradaic efficiencies of electrocatalytic reduction of ethanol by copper foam, cuprous selenide, 30-silver / cupperous selenide, 90-silver / cupperous selenide and 180-silver / cupperous selenide at various potentials were compared under carbon dioxide conditions.
[0086] Figure 5 The distribution diagram of the Faraday efficiency of ethanol under carbon dioxide conditions for copper foam, cuprous selenide, 30-silver / cuprous selenide, 90-silver / cuprous selenide, and 180-silver / cuprous selenide is shown. The selectivity of copper foam for ethanol is the lowest; after selenization, this situation is improved, and the selectivity of cuprous selenide for ethanol is significantly improved; while the loading of silver nanoparticles diversifies the active sites and changes the local charge distribution, thereby adjusting the interaction between the intermediate and the active site, thereby further improving the selectivity for ethanol. Among the silver / cuprous selenide composite catalysts, the 90-silver / cuprous selenide composite catalyst has the best Faraday efficiency for ethanol.
Claims
1. A silver nanoparticle / cuprous selenide composite catalyst, characterized in that: It is composited by cuprous selenide loaded with silver nanoparticles through electrodeposition, wherein the cuprous selenide is formed by treating foamed copper through chemical oxidation.
2. A method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 1, characterized in that: The following steps are involved: (1) placing the copper foam in acetone, hydrochloric acid and deionized water in turn and performing ultrasonic treatment to remove the oily substance and oxide layer on the surface of the copper foam; (2) preparing a mixed solution of sodium hydroxide and ammonium persulfate, and stirring and mixing; (3) soaking the copper foam treated in step (1) in the mixed solution obtained in step (2) to react until a layer of blue copper hydroxide is visible on the surface of the copper foam; (4) extracting the product in step (3), rinsing, and vacuum drying; (5) adding selenium powder, sodium borohydride and potassium hydroxide into deionized water, stirring and mixing at 40 to 60° C. to obtain a mixed solution; (6) placing the material obtained in step (4) into the mixed solution obtained in step (5), reacting at 100 to 150° C. for 4 to 6 hours, and then cooling to room temperature; (7) separating the product obtained in step (6), washing, and drying to obtain cuprous selenide; (8) Connecting the cuprous selenide obtained in step (7) as a working electrode to a three-electrode system, performing a scanning CV test, and reactivating the cuprous selenide; subsequently, applying a constant current to the cuprous selenide, with a deposition time of 30 to 180 seconds, to obtain a silver nanoparticle / cuprous selenide composite catalyst.
3. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: In the step (2), the concentration of sodium hydroxide in the mixed solution is 0.8 to 1.2 mol / L, and the concentration of ammonium persulfate is 0.05 to 0.1 mol / L, and the mixture is mixed for 5 to 10 minutes under magnetic stirring.
4. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: The reaction time in step (3) is 2 to 10 minutes.
5. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: In the step (5), the mixed solution has a selenium powder concentration of 0.02-0.05 mol / L, a sodium borohydride concentration of 0.05-0.1 mol / L, and a potassium hydroxide concentration of 0.02-0.05 mol / L. The solution is heated to 40-60° C. under magnetic stirring and stirred for 20-30 minutes.
6. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: The specific method of step (7) is as follows: separating the product obtained in step (6), washing it with deionized water for 2 to 3 times, and drying it; the drying temperature is 50 to 70° C., the drying time is 8 to 12 hours, and the drying condition is vacuum to obtain cuprous selenide.
7. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: The specific method of step (8) is as follows: preparing a mixed solution of citric acid trihydrate, silver nitrate and sulfuric acid, and stirring and dispersing the mixture; connecting the cuprous selenide obtained in step (7) as a working electrode to a three-electrode system consisting of a saturated calomel reference electrode and a platinum counter electrode, and using the mixed solution of citric acid trihydrate, silver nitrate and sulfuric acid as an electrolyte; performing a scanning CV test to reactivate the cuprous selenide; and then applying a constant current to the cuprous selenide for a deposition time of 30 to 180 seconds to obtain a silver nanoparticle / cuprous selenide composite catalyst.
8. The method for preparing the silver nanoparticle / cuprous selenide composite catalyst according to claim 2, characterized in that: The scanning CV test range in step (8) is 0.2 to -0.8 V (vs. SHE), and the constant current applied to cuprous selenide is 15 to 30 mA.
9. Use of the silver nanoparticle / cuprous selenide composite catalyst according to claim 1 in preparing a catalytic electrode.
10. Use of the silver nanoparticle / cuprous selenide composite catalyst according to claim 1 in electrocatalytic reduction of carbon dioxide.
Citation Information
Patent Citations
Sulfur ion doped cuprous selenide honeycomb-shaped flexible nanosheet array structure material, preparation method and application of sulfur ion doped cuprous selenide honeycomb-shaped flexible nanosheet array structure material
CN115072674A